Professional Standard "Demograph" as a Factor of Formation of a New Human Resources Model - Tamara K. Rostovskaya; Olga A. Zolotareva (Социологическая наука и социальная практика, 2021)
The article defines the prerequisites for the development of the professional standard “Demographer”, which is a fundamental stage for the formation of a new model of human resources in the field of demographic development. Content analysis of approved / valid documents revealed the absence of professional and educational standards for training specialists in the field of demography. Generalization and analysis of information on the subject area revealed existing problems, primarily in the field of public administration in the field of ensuring demographic security. The synthesis of modern methodological approaches made it possible to formulate the conclusion that demography as an independent type of activity (along with practical, scientific, etc.) has its own specialized (demographic) technologies and in modern conditions there is an urgent need to train professional personnel – “demographers”. Comparison of the All-Russian Classifier of Occupations (OKZ) with the International Standard Classification of Occupations 2008 (ISCO-08) and the International Standard Classification of Education (ISCED) and the emerging need for specialists-demographers were the basis for the implementation of the Institute for Demographic Research FCTAS RAS of an initiative project to develop a professional standard “Demographer”, which determines the conditions and opportunities for the development of education in the field of demography. The pool of developers makes it possible to formulate professional knowledge and skills (competencies) of both specific and interdisciplinary nature as much as possible, which determines the possibilities of work of demographers in various fields of science and practice. The professional standard “Demographer” will fully present and systematize uniform requirements for labor activity, as well as formulate requirements for graduates of professional educational organizations. The purpose of the study is to develop a systematic approach to the formation of a new model of human resources in the field of demographic development. The development of the professional standard “Demograf” is considered to be the basic stage in the formation of a modern system of training highly qualified personnel. As a result of the adoption / approval of the professional standard “Demographer”, the possibilities of training specialists-demographers will be revealed both within the framework of the currently implemented areas of education, and in the future, to single out an independent direction of preparation of higher education “Demographer”, to develop educational standards for the bachelor’s and master’s degrees.